In those days, at this time : holiness and history in the Jewish calendar - Segal, Eliezer (University of Calgary Press, 2007)
"In Those Days, At This Time is a collection of entertaining short essays that explores the intricate framework of sacred days and times that make up the Jewish festival calendar. Each piece is devoted to an occasion in the cycle of sacred seasons." "Segal investigates the ways festival observances have been shaped over the generations, looking at different interpretations of their rituals, their symbolism, and their adaptation to changing historical circumstances."--Jacket